دراسة تطبيق تقنية الEGR المبردة على محرك ديزل وأثرها على الملوثات الناجمة في شروط العمل المختلفة. - علي إيفا (Latakia University Journal -Engineering Sciences Series, 2018)
In this study circuit is designed and installed to measur the pollutants from the diesel engine in two stages at three speeds 1100, 1500, 1800rpm. When recycling rates range (0-70)% for no load. for load experiments, we measured the pollutants at the previous three speeds at 50% load values ​​and at full load. We were able to apply the load through a mechanism to apply the friction torque on a roller that was installed on the engine axis. We finally found that pollutants of all kinds are increasing by increasing the speed of circulation, as well as by increasing the applied load, and that the emissions of nitrogen oxides decrease the increase in the proportion of recycled gases, while the emissions of the remaining pollutants increase. تم في هذا البحث تصميم وتركيب الدارة وذلك لقياس بقياس الملوثات الناجمة عن محرك الديزل على مرحلتين وعند ثلاث سرعات 1800,1500, 1100rpm. وذلك عند نسب لإعادة التدوير تتراوح(0-70)% في تجارب اللاحمل. أما بالنسبة لتجارب الحمل فقد قمنا بقياس الملوثات عند السرعات الثلاث السابقة عند قيم حمل 50% وعند الحمل الكامل، واستطعنا تطبيق الحمل من خلال ميكانزم لتطبيق عزم احتكاك على بكرة تم تركيبها على محور المحرك. توصلنا في النهاية إلى ان الملوثات على مختلف أنواعها تزداد بزيادة سرعة الدوران، وكذلك بزيادة الحمل المطبق، وأن انبعاثات أكاسيد النتروجين تنخفض بزيادة نسبة الغازات المدورة في حين أن انبعاثات باقي الملوثات تزداد.